Injuries to the great vessels: an autopsy-based study - George, Thankamma P.; Sreedevi, C. S.; K., Sreekumari (International Journal of Research in Medical Sciences, 2020)
Background: Injuries of the chest causing disruption of the thoracic cage, damaging the great vessels are increasing daily. Aorta is most vulnerable to injury in deceleration trauma from road and air accidents, fall from height and penetrating injuries. Incidence of traumatic rupture of the aorta is rising with higher travel speed. Methods: In this study we analysed the pattern of injury to great vessels and the socio-demographic pattern of the victims in trauma. 250 cases brought to a tertiary care institution for autopsy were studied from 1st January 2005 to 30th November 2005 (1st July 2005 - 30th November prospectively, and 1st January - 30th June 2005, retrospectively). A cross sectional study design including all cases of trauma to the chest was done with consecutive sampling. Data was collected in pro forma and analysed. Results: 206 victims were males. Commonest cause of chest injury was trauma. 130 (52%) were victims of road traffic accidents and the vehicle implicated the most was bus (41 cases, 16.4%). Pedestrians constituted the majority (26.4%). 15 cases (6%) involved major blood vessels of the thorax. Descending part of the thoracic aorta was vulnerable, with transection of the great vessels in 5 cases (2%). Haemothorax was observed in 102 cases on right side and 94 cases on the left side. 9 cases (4%) of bronchial or tracheal ruptures with 6 cases of severance and 3 incidences of tear were recorded. Conclusions: The wound of aorta or pulmonary artery are immediately fatal and commonly seen in case of vehicular accident or fall from height due to the intense compression to the chest with or without any sign of external injury. Most ruptures are due to automobile accidents and the mechanism of injury is sudden motion of the heart and great vessels.